Chapter (what came about the mention of seal of the messenger of God, my God’s prayers and peace be upon him, from the book (Explanation of Shamail al-Nabawi) by Imam Lari – Study and Investigation - Otaifah, Ameera Ahmed Mohsen (Journal of Islamic Sciences, 2023)
This research aims to The brief definition of Imam al-Lari and his book: (Sharh al-Shama’il - Prophet Attributes), then verifying the text of the manuscript, chapter: (What came in the mention of the ring of the Messenger of God), eight hadiths were mentioned in this research: three in the two Sahihs, two hadiths in al-Bukhari, a hadith in Muslim, a hadith in the Musnad of Ahmad and al-Nasa’i which is authentic, and a hadith in Sunan Abi Dawood that scholars judged as weak. Where Imam Al-Lari took care of explaining these hadiths; So he collected its paths and explained its strangeness, and judged the hadith outside the books that adhered to authenticity, and translated it for the men of the chain of transmission, and relied, in explaining what is learned from the hadith, on the books of the predecessors such as al-Nawawi, Ibn Hajar, and others; Then this explanation appeared comprehensive For the originality of the content and the contemporary of the present. The research also concluded with some results and recommendations, which are more clear and strong in his conclusion.